When I grow up: assessing American children's perspectives on college and career readiness through drawings. (23rd March 2017) - Turner, Jennifer Danridge; Albro, Jennifer
Abstract: College and career readiness has become a key educational priority in the United States. Framed by neoliberal discourses, current conceptions of college and career readiness narrowly define literacy as discrete sets of cognitive skills and curricular knowledge and reduce literacy learning to scores on high‐stakes assessments. To disrupt these neoliberal ideologies, we invited 24 American children in a summer reading programme to share their perspectives on college and career readiness. Twelve boys and 12 girls created a series of drawings depicting their dream careers, the people helping them achieve their career goals and the specific literacy skills they perceived as necessary for future career success. Afterwards, the children discussed the meanings of their drawings through interviews. Analyses revealed that American children visually represented and verbally articulated college and career readiness as (1) aspiring towards productive professional work, (2) envisioning complex professional literacy repertories and (3) acknowledging the importance of family, community and school in college and career preparation. Our findings urge American schools to shift from standardised, high‐stakes measures of college and career readiness towards multiple, learner‐oriented measures which make visible the creativity, critical thinking and communicative literacies that children will need to fulfill their personal and professional aspirations.